Impact of Indonesia's Corn Import Restriction Policy on Feed Production Costs and Feed Price Dynamics in the Feedmill Industry - Tevi Melviana; Elly Tugiyanti; Novie Andri Setianto; Munasik Munasik; Yusmi Nur Wakhidati (ANIMAL PRODUCTION, 2026)
This study examines the impact of Indonesia's corn import ban on production costs and feed prices in the feedmill industry. Using a mixed-methods explanatory sequential design, we analyzed monthly time-series data from January 2020 to August 2025 (68 observations) obtained from the Indonesian Feedmill Association (GPMT) and Statistics Indonesia (BPS), and conducted in-depth interviews with five key industry stakeholders. Quantitative data were analyzed using multiple regression with the Cochrane-Orcutt transformation to correct for autocorrelation, log-log regression models to estimate elasticity, and descriptive statistics with volatility measures to assess seasonal patterns. Interview data were transcribed, coded using thematic analysis, and triangulated with the quantitative findings. The results show that the import ban significantly increased feed production costs, raising broiler feed costs by IDR 78.28/kg and layer feed costs by IDR 69.84/kg. Feed prices were highly inelastic to corn price changes, with elasticity coefficients of 0.030 for broiler feed and 0.064 for layer feed. The policy also increased volatility in corn availability and prices during off-harvest seasons (January–April and October–November). These findings suggest that although the policy aims to protect domestic corn farmers, it imposes substantial cost pressures on the downstream feed industry, underscoring the need for policy approaches that balance upstream and downstream interests.